2022
DOI: 10.2490/prm.20220004
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Iliopsoas Hematoma Caused by Prophylactic Anticoagulation against COVID-19

Abstract: Background: COVID-19 is associated with an increased risk of venous thromboembolism (VTE), and prophylactic anticoagulation is recommended for the prevention of VTE in COVID-19 patients. We encountered a patient with COVID-19 who developed iliopsoas hematoma (IPH) that was likely caused by prophylactic anticoagulation against VTE; we report the case here because IPH is an important risk in rehabilitation treatment. Case: The patient was a 73-year-old man with severe COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…In the case of surgical approaches for treating IPH, techniques including open surgery, interventional embolization, CT or ultrasound-guided puncture aspiration, and the injection of coagulation enzymes have been reported [10,22] . However, hematoma recurrence is a possibility with this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of surgical approaches for treating IPH, techniques including open surgery, interventional embolization, CT or ultrasound-guided puncture aspiration, and the injection of coagulation enzymes have been reported [10,22] . However, hematoma recurrence is a possibility with this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the study reported that the risk of VTE and bleeding was comparable in patients with COVID-19, but further randomized studies are needed to determine the optimal dose of thromboprophylaxis in patients with COVID-19. In a review of the literature, we found some case reports of IPH (iliopsoas hematoma) [ 4 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…These patients require comprehensive, multidisciplinary rehabilitation to regain their capacity for activities of daily living. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ) The survival rate of patients with COVID-19 varies depending on the strain, with infection with the Omicron strain resulting in a higher survival rate than that with the Delta strain. Recently, the overall survival rate of patients with COVID-19 has increased because of the prevalence of the Omicron strain.…”
Section: Introductionmentioning
confidence: 99%